2004
DOI: 10.1074/jbc.m310731200
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive Requirement for Transcription Factor IID-specific TAF-1 in Caenorhabditis elegans Embryonic Transcription

Abstract: The general transcription factor TFIID sets the mRNA start site and consists of TATA-binding protein and associated factors (TAF II s), some of which are also present in SPT-ADA-GCN5 (SAGA)-related complexes. In yeast, results of multiple studies indicate that TFIID-specific TAF II s are not required for the transcription of most genes, implying that intact TFIID may have a surprisingly specialized role in transcription. Relatively little is known about how TAF II s contribute to metazoan transcription in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 73 publications
(120 reference statements)
1
23
0
Order By: Relevance
“…Quantification of anti-Ser2-P was performed using the 3E10 antibody rather than H5 antibody because the H5 antibody recognizes an AMA-1-independent signal in mitotic nuclei that interferes with quantitative approaches (Walker et al, 2004); however, reported results were consistent between both antibodies.…”
Section: Immunofluorescencementioning
confidence: 84%
“…Quantification of anti-Ser2-P was performed using the 3E10 antibody rather than H5 antibody because the H5 antibody recognizes an AMA-1-independent signal in mitotic nuclei that interferes with quantitative approaches (Walker et al, 2004); however, reported results were consistent between both antibodies.…”
Section: Immunofluorescencementioning
confidence: 84%
“…Hence, the targeting of p300 by EIA of adenovirus abolishes this antiviral effect of STAT2 and indicates a significant role for this protein in cellular antiviral responses. Moreover, it was recently reported that interaction between P300 and TBP plays an important role in transcription and embryogenesis in yeast (Walker et al, 2004). In some recent studies p300 and PCAF have been found to have intrinsic histone acetyltransferase (HAT) activity and the ability to recruit additional HAT factors (Ji et al, 2003;Schiltz and Nakatani, 2000).…”
Section: Transcription and Translation Regulation Genesmentioning
confidence: 99%
“…In C. elegans, taf-4(RNAi) results in the most severe taf depletion phenotype, similar to that from depletion of RNA polymerase II (Walker and Blackwell, 2003; Walker et al, 2001; Walker et al, 2004). Therefore, efficient inactivation of TAF-4 would be an effective way to repress global transcription by RNA pol II.…”
Section: Discussionmentioning
confidence: 96%